Road Transportation of Fuel - Skopalová, Lenka; Novák, Radek, 1960-; Mervart, Michal, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
The thesis is concerned with road transportation of fuel. In theoretical part there are described the legal clauses that are related to this issue. The most detailed regulations can be found in the European Agreement on the International Carriage of Dangerous Goods by Road (so called Agreement ADR). Hence the biggest part of the theoretical section is devoted to these regulations. Instructions for transportation of diesel and petrol have been chosen from this international agreement and explained. Practical part deals with particular carrier of fuel - company Petrotrans s.r.o. Standard of service is compared according to several different customers, established demands on safety of fuel transportation are decribed and security of consumption tax in international fuel transportation is analysed.
Vedoucí práce: Radek Novák
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses